“I Worry About My Kids’ Safety When They Visit”: Mothers’ Perceptions of Father/Child Post-Separation Contact in the Context of IPV - Tutty, Leslie M. (Violence against women, 2025)
After separation because of intimate partner violence, fathers’ contact with children can be problematic. This mixed methods secondary analysis focused on 280 Canadian separated/divorced mothers who were 48.4% White, 45.1% Indigenous, and 6.5% Visible Minority. Of 176 fathers, 105 (59.7%) had regular visits and, 71 (40.3%) visited sporadically; 104 had no contact. Comments from half the mothers (54.3%) with regular father–child visits indicated worry, and 41.9% of all mothers perceived their children as sad/upset and another 14.5% as angry/acting out in response to visitation. Recommendations to address mothers’ and children's issues with respect to problematic father–child contact are provided.